1992
DOI: 10.1097/00006982-199212020-00015
|View full text |Cite
|
Sign up to set email alerts
|

Factors prognostic of Visual Outcome in Patients with Subretinal Hemorrhage

Abstract: Maslim J, et al. Limiting photoreceptor death and deconstruction during experimental retinal detachment: the value of oxygen supplementation. Am J Ophthalmol 1999;128:155-164. PURPOSE: To investigate the ocular manifestations of patients with severe acute respiratory syndrome (SARS) and to monitor the possible ocular complications arising from the treatment regimen with high-dose systemic corticosteroid drugs. DESIGN: Prospective, observational cohort case series. METHODS: Ninety eyes from 45 patients with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 0 publications
0
36
0
Order By: Relevance
“…1,2 The subretinal blood is a barrier to diffusion of oxygen from the choroid; contraction of the blood clot damages the photoreceptors; and the iron in the haemoglobin is toxic. 3 Bennett et al 4 found that patients with submacular haemorrhage associated with AMD involving the fovea had a mean visual acuity of 20/1700 at final follow-up. A number of interventions have been proposed, including intravitreal anti-VEGF alone, 5,6 intravitreal anti-VEGF combined with intravitreal gas and/or recombinant tissue plasminogen activator (rtPA), 7,8 and vitrectomy with subretinal rtPA and anti-VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The subretinal blood is a barrier to diffusion of oxygen from the choroid; contraction of the blood clot damages the photoreceptors; and the iron in the haemoglobin is toxic. 3 Bennett et al 4 found that patients with submacular haemorrhage associated with AMD involving the fovea had a mean visual acuity of 20/1700 at final follow-up. A number of interventions have been proposed, including intravitreal anti-VEGF alone, 5,6 intravitreal anti-VEGF combined with intravitreal gas and/or recombinant tissue plasminogen activator (rtPA), 7,8 and vitrectomy with subretinal rtPA and anti-VEGF.…”
Section: Introductionmentioning
confidence: 99%
“…The natural history of this condition is severe, with few patients showing much improvement in visual acuity. 1,2 Accumulation of blood in the subretinal space has been shown in experimental models to cause photoreceptor damage within 24 h, 3 and this may be because of shearing of photoreceptor outer segments, impaired transport of nutrients, and direct iron toxicity derived from haemoglobin. [2][3][4] Therefore, timely intervention is required.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Vitreoretinal surgery to remove subretinal blood secondary to neovascular AMD is associated with various complications including damage of retinal pigment epithelium. [4][5][6][7][8][9] Pharmacologically induced fibrinolysis does not significantly improve visual outcome.…”
Section: Introductionmentioning
confidence: 99%